Impact of Preprocessing of Graphene Additive via Ultrasonication on the Electrochemical Performance of Activated Carbon-Based Supercapacitors - Chameh, Behnam; Shaker, Majid; Shahalizade, Taieb; Sadeghi Ghazvini, Aliasghar; Saznaghi, Maryam Hemmati; Farhadi, Saeed; Shahroudi, Hamideh; Raissi, Babak; Aghaei, Alireza; Yaghmaee, Maziar Sahba; Riahifar, Reza (Energy Technology, 2023)
This article investigates the influence of the addition method of graphene to activated carbon (AC) on the electrochemical performance of the fabricated electric double-layer capacitors (EDLCs). To do so, the same graphene material is introduced to the other electrode slurry materials either in the form of a powder (GP) or a suspension (GL). It is discovered that the introduction of graphene already dispersed by ultrasonic in a suspension to AC has a better effect on the electrochemical performance of the fabricated EDLCs than directly employing its powder. GL EDLC achieves the highest capacitance of 54 F g−1 at a current density of 0.05 A g−1 in an organic electrolyte, which is much better than the GP EDLC (41.9 F g−1) and about 77% more than AC EDLC. Moreover, after cycling at various current densities (2000 cycles), GL EDLC maintains 28.8 F g−1 of its capacitance with 99.4% coulombic efficiency at a current density of 1 A g−1. Finally, GL EDLC exhibits 35.8 and 21.4 Wh kg−1 energy densities at 50.2 and 1102.8 W kg−1 power densities, respectively. The better performance of GL EDLC in comparison with GP EDLC is ascribed to better graphene dispersion.
CRIS-Team Scopus Importer:2023-09-29
Keywords: activated carbon; electric double-layer capacitors; graphene; ultrasonic dispersing